1997
DOI: 10.1248/cpb.45.1243
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Collagen by Singlet Oxygen Generated with UV-A.

Abstract: Singlet oxygen (1O2), a highly reactive and toxic intermediate, may play a role in photo-induced aging. We examined singlet oxygen generation from hematoporphyrin (HP) with UV-A, by monitoring the emission at 1,268 nm corresponding to 1O2 --> 3O2. Singlet oxygen was formed HP-dose-dependently in this system. We then investigated the reaction of singlet oxygen generated by UV-A irradiation with collagen, which is related to skin elasticity and softness. Collagen from skin was rapidly and dose-dependently cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Upon light exposure of the fluorescein, the collagen is rendererd resistant to dissolution in acid or tris buffer, likely due to the presence of additional cross-links that stabilize the collagen fibrils. Others have shown that both photo-generated singlet oxygen [3840] , generated by a reaction with singlet oxygen and fluorescein in its excited triplet state, or free-radicals [40] can react with histidine residues in collagen type I leading to the formation of stable cross-links. We also showed that one-photon (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Upon light exposure of the fluorescein, the collagen is rendererd resistant to dissolution in acid or tris buffer, likely due to the presence of additional cross-links that stabilize the collagen fibrils. Others have shown that both photo-generated singlet oxygen [3840] , generated by a reaction with singlet oxygen and fluorescein in its excited triplet state, or free-radicals [40] can react with histidine residues in collagen type I leading to the formation of stable cross-links. We also showed that one-photon (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Although skin components such as collagen and elastin, which are related to the resilience of skin, are degraded and generated by fibroblasts, chronic injury induced by ROS and lipid peroxide can cause functional and/or structural alterations of the collagen and elastin in the dermal layer, thus resulting in photoaging (2 -5). In particular, 1 O 2 , which is highly reactive and a toxic intermediate, may play a role in photo-aging (6). Therefore, the protection of fibroblasts from UVA or ROS generated by UV irradiation in the dermal layer may inhibit skin photo-aging.…”
Section: Discussionmentioning
confidence: 99%
“…Even though skin components such as collagen and elastin are degraded and generated by fibroblasts, chronic injury induced by ROS and lipid peroxide can cause functional and/or structural alterations of the collagen and elastin in the dermal layer, resulting in photo-aging (2 -5). In particular, 1 O 2 , which is a highly reactive and toxic intermediate, might play a role in photo-aging (6). UV is divided into three categories according to its wavelength: UVA (400 -315 nm), UVB (315 -280 nm), and UVC (<280 nm) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is also affected by singlet oxygen, whereby an increased hardening of collagen gels is observed accompanied by crosslinks between individual collagen strands. It is assumed that this effect is caused by interactions between photooxidised histidyl residues and amino groups of other amino acids [150]. This seems to be a highly specific reaction of collagen since other proteins like alcohol dehydrogenase are affected by singlet oxygen to a much lesser extent [150].…”
Section: Singlet Oxygenmentioning
confidence: 99%